Two signed seventeenth century icons of the Cretan school from the hermitage museum - Pyatnitsky Yuri (Zograf, 2012)
The article concerns the authorship of two Cretan icons from the ex-collection of Nikolay Likhachev held nowadays in the Hermitage museum. The iconography, stylistic features and techniques used in the icons prove dating to the seventeenth century. The first icon was signed by Ioannis Lampardos from Rethymnon. It has a rare iconography “Deisis - the Gate of Salvation”. The inscription on the second icon, the Virgin Lambovitissa, says that it was painted by hierodeacon Stephanos Tzankarolos. He is famous for his works created on the island of Corfu where he lived in the Holy Trinity monastery.